THE EFFECT OF PUSH UP TRAINING ON ARM MUSCLE STRENGTH IN BEGINNER RICH ROWING ATHLETES - Ayu, Puja Sri; Iyakrus, Iyakrus; Yusfi, Herri (Journal Physical Education, Health and Recreation, 2023)
This study aims to determine the effect of Push Up exercises on Arm Muscle Strength in Beginner Kayak Rowing Athletes in South Sumatra. The type of research used is a quasy experiment with a pretest “ posttest one group design. The independent variable is the push up exercise, the dependent variable is the arm muscle strength. The population of this study were beginner rowing athletes in South Sumatra. The sample of this research is 30 people. The instrument used is the flaxed “ arm hang test. The treatment in this study was in the form of push up exercises, after being given treatment for 6 weeks with a frequency of exercise 3 times a week. Based on the results of research and data analysis, from the results of the initial test (pretest) and the final test (posttest) there is an average increase of 0.18. And after testing the hypothesis with the t test statistic, with a significance level of 0.05, tcount 55.27 while ttable 1.70, then tcount > ttable, so it can be concluded that the push exercise with a time of 6 weeks with a frequency of exercise 3 times a week can increase strength. South Sumatra beginner rowing athlete. The implication of this study is that push up exercises can be used as a type of exercise to increase arm muscle strength.